Labor induction at 41+0 gestational weeks or expectant management for the nulliparous woman: The Finnish randomized controlled multicenter trial - Place, Katariina (John Wiley & Sons, 2025)
Introduction: Neonatal and maternal risks increase in term pregnancy as gestational age advances and become increasingly evident post-term. Management practices of late- and post-term pregnancies vary, and the optimal time point for intervention by labor induction is yet to be determined.
Material and methods: This randomized controlled trial of 381 nulliparous women with unripe cervices compared labor induction at 41+0 gestational weeks (early induction) with expectant management and labor induction at 41+5 to 42+1 gestational weeks (expectant management). This multicenter study included all five university hospitals and the largest central hospital in Finland. The study period was 2018–2022. Participants were randomized to either early induction (48.8%, n = 186) or expectant management (51.2%, n = 195) with equal randomization ratios of 1:1. This was a superiority trial, and the primary outcomes were rates of cesarean section (CS) and composite of adverse neonatal outcomes. The trial was registered at the ISRCTN registry (ISRCTN83219789, https://doi.org/10.1186/ISRCTN83219789).
Results: The rates of CS (16.7% [n = 31] vs. 24.1% [n = 47], RR 0.7 [95% CI: 0.5–1.0], p = 0.07) and a composite of adverse neonatal outcomes (9.7% [n = 18] vs. 14.4% [n = 28], RR 0.7 [95% CI: 0.4–1.2] p = 0.16) did not significantly differ between the groups, but the operative delivery rate was lower in the early induction group than in the expectant management group (30.6% [n = 57] vs. 45.6% [n = 89], p = 0.003). The rates of hemorrhage ≥1000 mL and neonatal weight ≥4000 g were also lower in the early induction group, as was the vacuum extraction rate in women with vaginal delivery. Of the women with expectant management, 45.6% (n = 89) had spontaneous onset of labor. No perinatal deaths occurred, but one case of eclampsia appeared in the expectant management group.
Conclusions: Offering labor induction to nulliparous women at 41+0 gestational weeks may decrease the probability of operative delivery, postpartum hemorrhage, and neonatal weight ≥4000 g. However, this study was underpowered to affirm the trends of rising rates of CS and adverse neonatal outcomes in the expectant management group. Thus, expectant management could remain an option for some, as one in two women with expectant management had a spontaneous onset of labor.